2019
DOI: 10.1074/jbc.ra118.005142
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence resonance energy transfer links membrane ferroportin, hephaestin but not ferroportin, amyloid precursor protein complex with iron efflux

Abstract: Edited by Ruma Banerjee Iron efflux from mammalian cells is supported by the synergistic actions of the ferrous iron efflux transporter, ferroportin (Fpn) and a multicopper ferroxidase, that is, hephaestin (Heph), ceruloplasmin (Cp) or both. The two proteins stabilize Fpn in the plasma membrane and catalyze extracellular Fe 3؉ release. The membrane stabilization of Fpn is also stimulated by its interaction with a 22-amino acid synthetic peptide based on a short sequence in the extracellular E2 domain of the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…In that study, the authors extended investigation of the idea that the protein product of the fAD locus AβPP stabilizes the iron exporting protein ferroportin, providing a connection between AβPP and iron homeostasis in AD. The idea that AβPP interacts with ferroportin has been the subject of some contention [81,82]. Tsatsanis et al observed that inhibition of the amyloidogenic cleavage of AβPP by the enzyme β-secretase in mouse N2a neuroblastoma cells is associated with stabilization of ferroportin on the cell surface and a reduced, intracellular labile iron pool.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the authors extended investigation of the idea that the protein product of the fAD locus AβPP stabilizes the iron exporting protein ferroportin, providing a connection between AβPP and iron homeostasis in AD. The idea that AβPP interacts with ferroportin has been the subject of some contention [81,82]. Tsatsanis et al observed that inhibition of the amyloidogenic cleavage of AβPP by the enzyme β-secretase in mouse N2a neuroblastoma cells is associated with stabilization of ferroportin on the cell surface and a reduced, intracellular labile iron pool.…”
Section: Discussionmentioning
confidence: 99%
“…Tau tangles in AD may also be a potential factor leading to iron dyshomeostasis and ferroptosis [80]. APP plays an important role in regulating the iron content of neurons; it promotes iron export by maintaining the stability of FPN [81, 82]. Iron status may directly impact the translation of APP through an iron-responsive mRNA element (IRE) in its 5′-UTR [83].…”
Section: The Role Of Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, despite significant differences in the liver iron content of anemic and FeDex-supplemented piglets, the level of hepcidin expression did not differ within the studied groups ( Figure 4 B). Fpn is able to form a functional complex with a copper-dependent, membrane-like protein that possesses ferroxidase activity—hephaestin (Heph) [ 42 ]. We found that in the intestine of anemic piglets, the level of Heph expression, both at the mRNA and protein level, was significantly lower compared to FeDex-supplemented piglets ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, even upon increased systemic iron demand, the transcriptional Hif-2α response can be reduced in the iron-rich duodenum. It has been proven in both in vitro and in vivo conditions that Smad4, an iron-dependent transcription factor, can limit Hif-2α transcriptional activity and iron deficiency leads to proteasomal degradation of Smad4 [ 42 ]. In the small intestine of mice fed iron-enriched, iron-replete, or low-iron diets, a dose-dependent decrease in Smad4 level has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%